Role of Pseudomonas aeruginosa Biofilm in the Development of Antibiotic Resistance in Escherichia coli - Raquid, Jillian Pia; Prieto, John Carlo; Arciaga, Danica Mae; Corpuz, Rica Hazel; Llorente, Shally Mae; Mabbayad, Jaira Marie; Sarmiento, Sophia Beatrix; Paraoan, Cielo Emar (Asian Journal of Biological and Life Sciences, 2018)
The study aimed to assess the role of Pseudomonas aeruginosa (P. aeruginosa) biofilm in the development of antimicrobial resistance of Escherichia coli (E. coli). P. aeruginosa (ATCC 27853) and E. coli (ATCC 25922) were cultured on cetrimide agar and eosin methylene blue (EMB) agar. The two microorganisms were mixed to prepare three bacterial suspensions using tryptic soy broth (TSB) in increasing concentrations, such as: 1:1, 2:3 and 1.5:3.5. Bacterial suspensions were transferred into MBEC™ Assay kits which was subjected to agitation and incubated at 37°C for 24 hrs and 48 hrs. Formed biofilms on peg lids were obtained for Gram staining and cultured using EMB agar to evaluate the biofilm matrix and presence of bacteria. Polymerase chain reaction (PCR) was conducted to determine significant changes in E. coli genes that matched the Tn1696 aacC1, Tn10 tetRA and Tn903 aph resistance genes of E. coli which codes for gentamicin, tetracycline and kanamycin, respectively. Results showed strong bands to Tn1696 aacC1 gene for gentamicin resistance at the highest concentration. No bands were visualized for tetracycline and kanamycin resistance. The results therefore establish that coexistence of both organisms in a biofilm leads to the development of the antimicrobial resistance of E. coli to gentamicin.
Keywords: Antimicrobial resistance; Biofilms; E. coli; P. aeruginosa